DEVELOPMENT OF NUMERIC LITERACY QUESTIONS IN SPLTV SUB DOMAIN FOR HIGH SCHOOL STUDENTS - Andini, Pungky Ayu; Nindiasari, Hepsi (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
This research aims to produce a numeracy literacy instrument in the three-variable linear equation system sub-domain for high school students that is valid, reliable, has distinguishing power and has a difficulty index. The research method used is the Research and Development (RD) method with modifications to the Wilson Oriondo and Antonio models. The research results obtained a numeracy literacy question instrument that was valid and reliable in the high category. They had differentiating power for 1 question that was insufficient information, 1 question that was in good condition, and three questions that were in perfect description. Apart from that, the questions also have a difficulty index, with two questions being easy, two being medium, and 1 question being difficult. So, the resulting instrument is suitable for measuring students' numeracy literacy.